Management of old tendo achilles injury by surgical reconstruction with Lindholm Technique - Choudhury, AI; Datta, NK; Kaiser, S; Tarafder, WH; Das, KP; Ahammed, S (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):213-8. The abstract of this article is available on the PubMed website